Reverend Dr. Martin Luther King, Jr. March in Downtown Fresno to Saroyan Theatre - Watkins, Howard::::::::: (1985)
Front of march across with dignitaries locking arms the width of M Street at Mariposa Mall City Hall on Fresno Street and Brix Apartments in background